2020
DOI: 10.1371/journal.pgen.1008623
|View full text |Cite
|
Sign up to set email alerts
|

Comparing DNA replication programs reveals large timing shifts at centromeres of endocycling cells in maize roots

Abstract: Plant cells undergo two types of cell cycles–the mitotic cycle in which DNA replication is coupled to mitosis, and the endocycle in which DNA replication occurs in the absence of cell division. To investigate DNA replication programs in these two types of cell cycles, we pulse labeled intact root tips of maize ( Zea mays ) with 5-ethynyl-2’-deoxyuridine (EdU) and used flow sorting of nuclei to examine DNA replication timing (RT) during the transition from a mitotic cycle to an endocycle.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 132 publications
(234 reference statements)
0
4
0
Order By: Relevance
“…Disruption of the replication initiation factors ORC2 or GINS2 has also been shown to induce polyploidization in human cells ( Rantala et al 2010 ; Huang et al 2016 ). Similarly, it was recently shown that ∼2% of the maize genome is delayed in its replication in endocycles compared to normal mitotic cycles ( Wear et al 2020 ). Polyploidization is also very common in cancer ( Bielski et al 2018 ), and so is replication stress; it is intriguing to consider whether these two phenomena are related to each other.…”
Section: Discussionmentioning
confidence: 93%
“…Disruption of the replication initiation factors ORC2 or GINS2 has also been shown to induce polyploidization in human cells ( Rantala et al 2010 ; Huang et al 2016 ). Similarly, it was recently shown that ∼2% of the maize genome is delayed in its replication in endocycles compared to normal mitotic cycles ( Wear et al 2020 ). Polyploidization is also very common in cancer ( Bielski et al 2018 ), and so is replication stress; it is intriguing to consider whether these two phenomena are related to each other.…”
Section: Discussionmentioning
confidence: 93%
“…Disruption of the replication initiation factors ORC2 or GINS2 has also been shown to induce polyploidization in human cells (Huang et al, 2016; Rantala et al, 2010). Similarly, it was recently shown that ~2% of the maize genome is delayed in its replication in endocycles compared to normal mitotic cycles (Wear et al, 2020). Polyploidization is also very common in cancer (Bielski et al, 2018), and so is replication stress; it is intriguing to consider whether these two phenomena are related to each other.…”
Section: Discussionmentioning
confidence: 92%
“…Together with dense DNA methylation, centromeres typically share other features of classical heterochromatin, including cytological condensation and late DNA replication ( Schubert et al 2020 ; Wear et al 2020 ). It should also be noted that many eukaryotes, including budding yeast, fission yeast, D. melanogaster , and C. elegans lack detectable DNA cytosine methylation, although other chromatin marks, including H3K9me3, can function to suppress transposons in its place ( Gutbrod and Martienssen 2020 ).…”
Section: Dna Methylation and Centromeric Epigenetic Statesmentioning
confidence: 99%